Social Design and Neocolonialism - and Janzer, Cinnamon L.; Weinstein, Lauren S. (Design and Culture, 2014)
This article examines the current field of social design: its claims, practices, and methodologies. Findings discovered through qualitative research illuminate the current application of social design practices and offer critique around their use in the social sphere. This article argues that designers must be sensitive to a variety of complex social and cultural cues and structures or they risk contributing to, or practicing, design neocolonialism. The article offers two key theoretical suggestions to further the emerging field's progress. First, social design must shift its focus from one that is human-centered to one that is situation-centered. Second, it is imperative that social design develops a shared framework for understanding, executing, and evaluating its initiatives and interventions. Additionally, this article introduces a matrix to serve as an early iteration of a shared framework.
Keywords: Design Methodology; Design Thinking; Framework; Human-centered design; IMPORTANT; social design